Isolation and Characterization of flavonoids Luteolin and Quercetin from the leaves of Piper betle var Magahi - Singh Nadkar Narayan singh; Jitendra Singh; Alok Mukharjee (International Journal of Medical Toxicology and Legal Medicine, 2023)
Background and Objectives: Plants are a rich source of diverse chemical compounds with potential therapeutic properties. Phytopharmaceuticals offer a vast array of bioactive constituents that can be used to develop new drugs or as alternative treatments to conventional medicines. Plant-derived compounds often exhibit diverse pharmacological activities, such as anti-inflammatory, antimicrobial, antioxidant, anticancer, analgesic, and immunomodulatory properties. S Methods: Isolated ethanolic extract from Piper betle var Magahiwas dissolved in 5.0 ml of 2.0 N hydrochloric acid, 0.04% (w/v) ascorbic acid as an antioxidant was added to 50mL of semi solid sample then heated at 90ºC for 2 hours. Aallowed to cool and sonicated for 5 minutes to remove the dissolved oxygen. The extract was cooled, filtered using Buchner filter.By using column chromatography, HPTL, NMR, IR spectroscopy and mass spectroscopy process of isolation was completed. Result: Isolated sample were compared with standard one and also compared with previous reported data of isolated Luteolin and Quercetin. Conclusion: The result of present study established the presence of biologically active compounds Luteolin and Quercetin in the leaves of Piper betle variety Magahi. The data suggest that the significant amount of biologically active compound present in the leaves of Piper betle varity Magahi.